Stage‐dependent thyroxine effects on sea urchin development - Leland G. Johnson (New Zealand Journal of Marine and Freshwater Research, 1998)
Thyroxine, one of the iodinated hormones produced by vertebrate thyroids, has been reported to accelerate late larval development in several sea urchins (Chino et al. 1994) and in the crown‐of‐thorns starfish (Johnson & Cartwright 1996), but thyroxine effects on earlier portions of echinoderm development have not been reported. I investigated thyroxine effects on developmental rates during several periods spanning development from early cleavage to metamorphosis in the New Zealand sea urchin Evechinus chloroticus (Valenciennes). Thyroxine treatment slowed development between the eight‐cell stage and assembly of the four‐armed pluteus and mid‐larval development between the four‐armed and six‐armed stages. Thyroxine treatment accelerated progress of eight‐armed plutei toward settling, but did not alter the final percentages of larvae that settled and metamorphosed to juvenile urchins. Acceleration of late larval echinoderm development by thyroxine may indicate a relatively ancient evolutionary origin of thyroxine's effects on developmental processes (Johnson 1997).